2016
DOI: 10.21873/anticanres.11057
|View full text |Cite
|
Sign up to set email alerts
|

Insurance Status and Other Non-biological Factors Predict Outcomes in Acute Myelogenous Leukemia: Analysis of Data from the National Cancer Database

Abstract: We observed that payer status has a statistically significant relationship with overall survival from AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 32 publications
(42 reference statements)
1
13
0
Order By: Relevance
“…We observed that even for the same leukemia subtype, the survival rate would gradually decrease with the increase in age of diagnosis, which is somewhat consistent with prior studies that demonstrated worsening survival among the older population, compared to the younger population [11,21,27,31]. In particular, among above-75 leukemia patients other than CLL the 5-year relative survival rate is almost below 45% in 2012, which partly may be explained as the patients with other comorbidities, prior organ dysfunction, and unbearable for intensive chemotherapy, lack of insurance [32][33][34][35]. As a result, new therapeutic strategies, such as monoclonal antibodies, CAR-T cells, better supportive care, more effective disease monitoring, and combinations with other investigational agents, need be developed and verified to improve the prognosis of all leukemia types, especially in the elder patients [7,20,32].…”
Section: Discussionsupporting
confidence: 86%
“…We observed that even for the same leukemia subtype, the survival rate would gradually decrease with the increase in age of diagnosis, which is somewhat consistent with prior studies that demonstrated worsening survival among the older population, compared to the younger population [11,21,27,31]. In particular, among above-75 leukemia patients other than CLL the 5-year relative survival rate is almost below 45% in 2012, which partly may be explained as the patients with other comorbidities, prior organ dysfunction, and unbearable for intensive chemotherapy, lack of insurance [32][33][34][35]. As a result, new therapeutic strategies, such as monoclonal antibodies, CAR-T cells, better supportive care, more effective disease monitoring, and combinations with other investigational agents, need be developed and verified to improve the prognosis of all leukemia types, especially in the elder patients [7,20,32].…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, two US acute leukemia studies conducted in completely different settings have previously found comparable results. Master et al13 examined 67,443 AML patients and found no survival difference between patients living <30 vs >30 miles from the treatment center (HR for OS=0.99; 95% CI=0.99–1.02),whereas Rodriguez et al,12 in a single center study including only 281 intensive therapy AML patients, found no correlation of OS with an increase in distance to treatment center by 20 mile intervals (HR for OS=0.99; 95% CI=0.98–1.02). Though these studies imply that distance, also in large countries with insurance-based healthcare, does not affect treatment and outcomes in AML, bias and important methodological limitations might explain the results in selected cohorts of patients who are able to make it to these treatment centers.…”
Section: Discussionmentioning
confidence: 99%
“…As such, two previous studies investigated the impact of distance to treatment center in AML patients and found no effect on survival 12,13. Limitations included lack of individual-level socioeconomic-, cytogenetic-, and treatment information, as well as small and selected populations.…”
Section: Introductionmentioning
confidence: 98%
“…For example, a historical cohort study conducted on patient records included in the US National Trauma Data Bank shows that the health insurance type independently affects the outcome and mortality rate of patients, with uninsured and publicly insured patients at a significantly higher risk of in‐hospital mortality compared with privately insured patients . In another study on more than 65 000 patients registered in the US National Cancer Database with the diagnosis of acute myeloid leukemia, after adjusting for confounding variables, insurance type was found to be an independent predictor of mortality in patients; those privately insured had the lowest mortality compared with patients with Medicaid and those without insurance …”
Section: Discussionmentioning
confidence: 99%
“…12 In another study on more than 65 000 patients registered in the US National Cancer Database with the diagnosis of acute myeloid leukemia, after adjusting for confounding variables, insurance type was found to be an independent predictor of mortality in patients; those privately insured had the lowest mortality compared with patients with Medicaid and those without insurance. 13 For the calculation of YLL, we used the life expectancy table of Japanese people. 6,7 If we would have calculated the YLL based on the life expectancy table of Iranian people, which has a lower life expectancy than the Japanese, we came to even a lower YLL value.…”
Section: Discussionmentioning
confidence: 99%